2016
DOI: 10.1007/978-3-319-39225-7_12
|View full text |Cite
|
Sign up to set email alerts
|

Herding Cats: A Case Study of Release Management in an Open Collaboration Ecosystem

Abstract: Part 1: Full PapersInternational audienceRelease management in large-scale software development projects requires significant communication and coordination. It is particularly challenging in Free and Open Source Software (FOSS) ecosystems, in which hundreds of loosely connected developers and their projects need to be coordinated to release software to a schedule. To better understand this process and its challenges, we analyzed over two and half years of communication in the GNOME ecosystem and studied devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Within literature examining design and implementation of information systems the focus on political issues concentrated more on the organizational change, managerial practices, and political tactics to resist change [17,18]. In software engineering some research has been carried out to investigate power and politics in different areas such as requirements engineering [11,19], and software eco-systems [20,21]. In a study by Bano, Zowghi, & Ramini, [16] the political aspects of the relationship between user involvement and system success has been studied .…”
Section: Power and Politics In Information Technology Disciplinesmentioning
confidence: 99%
“…Within literature examining design and implementation of information systems the focus on political issues concentrated more on the organizational change, managerial practices, and political tactics to resist change [17,18]. In software engineering some research has been carried out to investigate power and politics in different areas such as requirements engineering [11,19], and software eco-systems [20,21]. In a study by Bano, Zowghi, & Ramini, [16] the political aspects of the relationship between user involvement and system success has been studied .…”
Section: Power and Politics In Information Technology Disciplinesmentioning
confidence: 99%
“…The 10th Annual Future of Open Source Survey [2] showed that 65% of the surveyed companies leverage FOSS to speed up application development, and 55% leverage FOSS for production infrastructure. On the other hand, the movement has introduced new challenges [3][4][5][6][7], especially in relation to openness and the innovative nature of this development model.…”
Section: Introductionmentioning
confidence: 99%